2007
DOI: 10.1152/jn.00332.2007
|View full text |Cite
|
Sign up to set email alerts
|

Quantal and Nonquantal Transmission in Calyx-Bearing Fibers of the Turtle Posterior Crista

Abstract: Intracellular recordings were made from nerve fibers in the posterior ampullary nerve near the neuroepithelium. Calyx-bearing afferents were identified by their distinctive efferent-mediated responses. Such fibers receive inputs from both type I and type II hair cells. Type II inputs are made by synapses on the outer face of the calyx ending and on the boutons of dimorphic fibers. Quantal activity, consisting of brief mEPSPs, is reduced by lowering the external concentration of Ca 2+ and blocked by the AMPA-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
108
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 82 publications
6
108
0
1
Order By: Relevance
“…Similarly, in somas of vestibular ganglion cells, spontaneous firing was not seen in whole-cell patch-clamp recordings, and action potentials were only evoked by current injections (Limón et al 2005;Risner and Holt 2006;Iwasaki et al 2008). These data are in contrast to intracellular and extracellular microelectrode recordings which have demonstrated spontaneous firing in vestibular afferents Holt et al 2007a;Lysakowski et al 1995). Previous results have indicated that the half-inactivation voltage for the Na + current in calyx terminals is quite negative, with a mean value of −83 mV (Rennie and Streeter 2006).…”
Section: Effects Of 4-ap and Tea On Action Potentialsmentioning
confidence: 84%
See 2 more Smart Citations
“…Similarly, in somas of vestibular ganglion cells, spontaneous firing was not seen in whole-cell patch-clamp recordings, and action potentials were only evoked by current injections (Limón et al 2005;Risner and Holt 2006;Iwasaki et al 2008). These data are in contrast to intracellular and extracellular microelectrode recordings which have demonstrated spontaneous firing in vestibular afferents Holt et al 2007a;Lysakowski et al 1995). Previous results have indicated that the half-inactivation voltage for the Na + current in calyx terminals is quite negative, with a mean value of −83 mV (Rennie and Streeter 2006).…”
Section: Effects Of 4-ap and Tea On Action Potentialsmentioning
confidence: 84%
“…How the calyceal synapse operates remains enigmatic. Detection of excitatory postsynaptic currents (EPSCs) in solitary gerbil calyces (Rennie and Streeter 2006) and CNQX-sensitive potentials in turtle vestibular afferents support α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-mediated quantal transmission at this synapse (Bonsacquet et al 2006;Holt et al 2007a). Furthermore, in common with other hair cells from the auditory and vestibular systems, there are several ribbon synapses within type I hair cells and their calyces which provide the synaptic machinery for chemical neurotransmission (Lysakowski and Goldberg 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic transmission between type II cells and their terminals is chemically mediated and quantal (12,13). Synaptic transmission between type I cells and their calyces has a quantal glutamatergic component (13)(14)(15)(16)(17) augmented by a nonquantal excitatory postsynaptic current (nqEPSC) (14,16). It was hypothesized previously that the ball-and-socket morphology of the hair cell-calyx terminal might lead to the nqEPSC through stimulus-evoked modulation of the ½K + within the synaptic cleft (18)(19)(20).…”
mentioning
confidence: 99%
“…The discharge of the eighth nerve sensory neurons in the absence of stimulation is thought to arise from a steady excitation due to background calciumdependent release of neurotransmitter from presynaptic hair cells (Adrian 1943;Annoni et al 1984;Flock and Russel 1976;Furukawa et al 1972;Furukawa and Ishii 1967;Harris and Flock 1967;Holt et al 2006Holt et al , 2007Hudspeth 1986;Ishii et al 1971;Katz 1969;Rossi et al 1977;Schessel et al 1991;Siegel 1992;Siegel and Dallos 1986; see recent review by Fuchs and Parsons 2006 regarding the details of synaptic release and physiology). The release of chemical neurotransmitter into the synapse by hair cells is thought to produce a steady background excitation of primary afferent dendrites and in turn lead to action potential discharge patterns.…”
Section: Introductionmentioning
confidence: 99%